'It Runs in the Family'. Exploring Contagious Kinship Connections. Issue 4 (7th August 2020) - Meinert, Lotte; Grøn, Lone
ABSTRACT: In this introduction we conceptualise phenomena that tend to 'run in the family' as contagious kinship connections arguing that experiences of such contagious connections often resemble experiences of haunting. We propose that enigmas about what family is, and what happens in the sociality and practice of kinship and descent, can be understood as forms of social contagion and affective transmission. The empirical contributions of this issue examine what appears if we explore kinship through the analytical lens of contagious connections and vice versa: if we explore contagion in kinship and family. In the introduction we suggest to explore contagious kinship connections through crosscutting questions about WHAT runs in families; HOW 'it' runs; what kinship IS, then; and what people DO about contagious kinship connections.